Narrativas interativas digitais na prevenção do suicídio - Viganó, Mariana Ruaro (My University, 2019)
The present work investigates the potential use of interactive narratives in suicide prevention. Interactive narratives are contextualized as histories that need action of the interagent to build the plot. With theoretical conceptualizations about interactivity, immersion and non-linear texts. Suicide, recognized as a worldwide problem, is understood in the research by their warning signals, association with adolescents, Brazilian scenario and main resources for prevention. The information collected provided subsidies for the development of a solution which consists on the creation of one interactive narrative focused on suicide prevention among adolescents seeking to provide emotional support and information about the theme. The validation through questionnaires contemplated two distinct groups young who testified over the relevance and knowledge of the subject and mental health experts who attested the content, format and application of the narrative. The results revealed that the model would be able to clarify concepts relevant to prevention. The existence of choices favor the identification of the interagent with the story and assists in risk control and guidance for seeking appropriate treatment (sic).
O presente trabalho investiga o potencial do uso de narrativas interativas digitais na prevenção do suicídio. As narrativas interativas se contextualizam como histórias que necessitam da ação do interagente para construção do enredo. Com conceituações teóricas acerca de interatividade, imersão e textos não lineares. O suicídio, reconhecido como um problema mundial de saúde, é compreendido na pesquisa pelos seus sinais de alerta, associação com adolescência, cenário brasileiro e principais recursos para prevenção. As informações coletadas forneceram subsídios para o desenvolvimento de uma solução que consiste na criação de uma narrativa interativa focada na prevenção do suicídio entre adolescentes e buscando proporcionar apoio emocional e informações a respeito do tema. A validação por meio de questionários contemplou dois grupos distintos jovens que atestaram sobre a relevância e o conhecimento do assunto e especialistas da área de saúde mental atestaram o conteúdo, formato e aplicação da narrativa. Os resultados revelaram que o modelo estaria apto a esclarecer conceitos relevantes para a prevenção. A existência de escolhas facilita a identificação do interagente com a história e auxilia no controle de risco e orientação para busca de um tratamento adequado (sic).
Keywords: Suicídio; Narrativa; Narrativas digitais; Suicídio - Prevenção